2008
DOI: 10.3748/wjg.14.2602
|View full text |Cite
|
Sign up to set email alerts
|

Systemic gemcitabine combined with intra-arterial low-dose cisplatin and 5-fluorouracil for advanced hepatocellular carcinoma: Seven cases

Abstract: The combination of intra-arterial low-dose cisplatin and 5-fluorouracil (5-FU) is effective against advanced hepatocellular carcinoma (HCC). Systemic gemcitabine chemotherapy seems effective in many cancers. We report the results of combination therapy with systemic gemcitabine, intra-arterial low-dose cisplatin and 5-FU (GEMFP). Seven patients with non-resectable advanced HCC were treated with GEMFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The response rates obtained in the present study were similar to those obtained in the report by Uka et al [21] and lower than those obtained in the other two reports. This discrepancy may be explained by the different criteria used to evaluate antitumor efficacy, as Uka et al [21] suggested in their discussion. Obi et al [13] and Ota et al [18] used the Eastern Clinical Oncology Group criteria, whereas Uka et al [21] and the present study used the Response Evaluation Criteria in Solid Tumors.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The response rates obtained in the present study were similar to those obtained in the report by Uka et al [21] and lower than those obtained in the other two reports. This discrepancy may be explained by the different criteria used to evaluate antitumor efficacy, as Uka et al [21] suggested in their discussion. Obi et al [13] and Ota et al [18] used the Eastern Clinical Oncology Group criteria, whereas Uka et al [21] and the present study used the Response Evaluation Criteria in Solid Tumors.…”
Section: Discussionsupporting
confidence: 64%
“…This discrepancy may be explained by the different criteria used to evaluate antitumor efficacy, as Uka et al [21] suggested in their discussion. Obi et al [13] and Ota et al [18] used the Eastern Clinical Oncology Group criteria, whereas Uka et al [21] and the present study used the Response Evaluation Criteria in Solid Tumors.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations